2009
DOI: 10.1111/j.1472-765x.2009.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of frog antimicrobial peptides by extracellular products of the bacterial pathogenAeromonas hydrophila

Abstract: Aims:  To determine whether the extracellular products (ECPs) from Aeromonas hydrophila, a frog bacterial pathogen that is resistant to skin antimicrobial peptides of three different frog species Xenopus laevis, Litoria aurea and Litoria raniformis, can modulate the activity of these peptides. Methods and Results:  ECPs were collected from cultures of Klebsiella pneumoniae, a pathogen susceptible to skin antimicrobial peptides of all three tested frog species, and from cultures of Aer. hydrophila. They were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
(24 reference statements)
1
14
0
Order By: Relevance
“…This organism shows antifungal characteristics including activity against Bd growth [33]. The ability of extracellular products of A. hydrophila to inhibit amphibian antimicrobial peptides indicates a co-evolutionary relationship between host and symbionts [59]. In addition, Pseudomonas mirabilis and Serratia liquefaciens were found to be resistant to antimicrobial peptides from several host frog species [60].…”
Section: Discussionmentioning
confidence: 99%
“…This organism shows antifungal characteristics including activity against Bd growth [33]. The ability of extracellular products of A. hydrophila to inhibit amphibian antimicrobial peptides indicates a co-evolutionary relationship between host and symbionts [59]. In addition, Pseudomonas mirabilis and Serratia liquefaciens were found to be resistant to antimicrobial peptides from several host frog species [60].…”
Section: Discussionmentioning
confidence: 99%
“…and Ribeiroia ondatrae . Although the Gram-negative bacterium A. hydrophila is not inhibited by amphibian skin peptides tested to date (Rollins-Smith et al ., 2002; Schadich and Cole, 2009; Tennessen et al ., 2009), both ranaviruses and Bd can be inhibited (Rollins-Smith et al ., 2002; Chinchar et al ., 2004). The ability of tadpole peptides to inhibit other bacterial pathogens, protozoa or fungal infections, such as S. ferax (Romansic et al ., 2006), remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Host endopeptidases are produced by some amphibians to degrade peptides, or to cleave propeptides in order to activate their antimicrobial potential (Resnick et al, 1991 Mignogna et al, 1996;Steinborner et al, 1997). In addition, some pathogens can deactivate AMPs as part of an immune evasion strategy (Kraus and Peschel, 2008;Schadich and Cole, 2009). Indeed, recent studies with Rana pipiens have shown that 60 min after secretion onto the skin some AMPs are cleaved and their ability to inhibit Bd growth is diminished (Pask et al, 2012).…”
Section: Discussionmentioning
confidence: 99%